2009
DOI: 10.2353/ajpath.2009.080947
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy Inhibits Remyelination in the Central Nervous System

Abstract: Remyelination of lesions in the central nervous system contributes to neural repair following clinical relapses in multiple sclerosis. Remyelination is initiated by recruitment and differentiation of oligodendrocyte progenitor cells (OPCs) into myelinating oligodendrocytes. Simvastatin, a blood-brain barrierpermeable statin in multiple sclerosis clinical trials, has been shown to impact the in vitro processes that have been implicated in remyelination. Animals were fed a cuprizone-supplemented diet for 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
82
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 38 publications
15
82
0
Order By: Relevance
“…Some studies also support the key role of remyelination in promoting neuronal survival after injury to adult CNS. 33 In the present study, abundant myelin sheaths were identified by double-immunostaining in the PLGA-SF-NT-3 group, but not in the control groups. Furthermore, the formation of myelin structure was also supported by EM analysis, which revealed robust myelinated axons in the PLGA-SF-NT-3 group.…”
mentioning
confidence: 79%
“…Some studies also support the key role of remyelination in promoting neuronal survival after injury to adult CNS. 33 In the present study, abundant myelin sheaths were identified by double-immunostaining in the PLGA-SF-NT-3 group, but not in the control groups. Furthermore, the formation of myelin structure was also supported by EM analysis, which revealed robust myelinated axons in the PLGA-SF-NT-3 group.…”
mentioning
confidence: 79%
“…In contrast to statin-mediated inhibition of cholesterol synthesis, which raises some concerns about the inhibition of remyelination in the CNS (38), Rho kinase inhibitors may provide a desired selective inhibition of the key pathogenic cytokines, which drive the autoimmune response in MS. Because Rho kinase expression is induced by inflammatory stimuli and Rho expression is increased in MS lesions (39), the selective Rho kinase inhibitors represent a promising therapeutic approach (40) that requires further clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Statins and inhibitors of receptor tyrosine phosphatases are other pharmacologic agents that induce rodent [111] and human [112] oligodendrocyte differentiation. However, when tested in the cuprizone model of demyelination in vivo, statin therapy inhibited remyelination [113]. Olig1 is an important transcription factor in early oligodendrocyte specification and differentiation.…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%